Quality control in aerobiological networks - Galan, Carmen (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Nowadays the information generated by the aerobiological networks should be adapted to the quality control standards according to the International Standards Organisation (ISO) rules 9001:2000. The quality control guidelines proposed by the ISO are addressed to the aerobiological network to guarantee standardized, accurate and valuable data.